2013
DOI: 10.1186/1687-9856-2013-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of continuous glucose monitoring in the care of children with type 1 diabetes

Abstract: Continuous glucose monitoring (CGM), while a relatively new technology, has the potential to transform care for children with type 1 diabetes. Some, but not all studies, have shown that CGM can significantly improve hemoglobin A1c levels and reduce time spent in the hypoglycemic range in children, particularly when used as part of sensor-augmented pump (SAP) therapy. Despite the publication of recent clinical practice guidelines suggesting CGM be offered to all children 8 years of age or older who are likely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Conversely, the iPro2 is calibrated retrospectively, so one would expect the same disturbances to have less impact on the overall accuracy, as future calibration BG values are known. Overall, the MARD values presented here are all in the region of reported MARD for CGM in outpatients, where the devices were designed to be used (Kovatchev et al, 2008, Larson andPinsker, 2013), indicating that they otherwise performed as might be expected despite the different cohort.…”
Section: Overall Cohortmentioning
confidence: 71%
“…Conversely, the iPro2 is calibrated retrospectively, so one would expect the same disturbances to have less impact on the overall accuracy, as future calibration BG values are known. Overall, the MARD values presented here are all in the region of reported MARD for CGM in outpatients, where the devices were designed to be used (Kovatchev et al, 2008, Larson andPinsker, 2013), indicating that they otherwise performed as might be expected despite the different cohort.…”
Section: Overall Cohortmentioning
confidence: 71%
“…Among children there was an absolute reduction in HbA 1c of 0.4 ± 0.9% in the SAP therapy group and an increase of 0.2 ± 1.0% in the MDI group. Several other RCTs have confirmed that SAPs improve glucose control at no increased risk of hypoglycemia in pediatric patients [19][20][21]. Therefore, age does not seem to be a factor for the success of SAP therapy.…”
Section: Influence Of Agementioning
confidence: 88%
“…At entry, 90 patients in each group had a normal albumin excretion rate and 20 had persistent microalbuminuria. The albumin excretion rate [median (95% CI)] was similar at baseline [6.0 μg/min (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) in the CSII group vs. 4.4 (8)(9)(10)(11)(12)(13)(14)(15)(16) in the MDI group, NS] and significantly lower in the patients treated with CSII, both at year 2 and at year 3 of follow-up [4.7 μg/min (6-12) vs. 6.4 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), p < 0.002]. Nine patients progressed to microalbuminuria in the MDI group while only 1 did in the CSII group.…”
Section: Long-term Complicationsmentioning
confidence: 98%
“…In spite of being the most advanced technology, CGM and SAP are still rarely used in routine care of children and adolescents with type 1 diabetes mellitus (Type 1 DM) [4,5].…”
Section: Introductionmentioning
confidence: 99%